Pigmentary glaucoma treatment - Aydın, Ali Ekrem (Gazi Göz Vakfı, 2020)
Pigment dispersion syndrome (PDS) is a clinical entity that is characterized with anomalous irido-zonular contact leading pigment dispersion throughout the anterior segment. Clinical presentation includes pigmented cells on the corneal endothelium, an increased pigmentation of the trabecular meshwork, and mid-periphery transillumination defects of iris. The syndrome is usually bilateral and more common in myopic individuals and young male adults. Also it can be associated with ocular hypertension or glaucoma. Pigmentary glaucoma (PG) is a kind of secondary open-angle glaucoma and is caused by occlusion of trabecular meshwork by pigmentary cells and reduction in the aqueous humor effl ux. In this review, we will discuss clinical characteristics, pathogenesis and current management of PDS and PG.
Keywords: Pigmentary Glaucoma Treatment; Eye Diseases